A numerical study on the hydrodynamic impact of device slenderness and array size in wave energy farms in realistic wave climates. (15th September 2017) - Penalba, Markel; Touzón, Imanol; Lopez-Mendia, Joseba; Nava, Vincenzo
Abstract: The future of wave energy converters lies in the design and realization of farms comprising of several devices, given the level of actual power flow for the individual devices and because of several operational issues. Therefore, not only the hydrodynamics of individual and isolated devices should be analysed, but interactions among devices within an array must also be carefully evaluated. In this paper, the authors attempt to parameterize the behaviour of small-, medium- and large-arrays of wave energy converters, in a particular staggered configuration, at four different locations characterized by realistic wave climates. The arrays studied in the present paper consist of heaving cylinders of different slenderness ratios. It turns out that for arrays of very short inter-device distances, regardless of the cylinder and array size, interactions are strong and lead to not negligible effects of destructive interference (total power reduction compared to the sum of isolated devices). Under these conditions, the bigger the array, the stronger the interactions and the higher the loss of power. However, a range of inter-device distances, referred to as intermediate region, where the power absorption is consistent and the interaction effect appears to be positive, has been found. This intermediate region is easily detectable for small arrays, but loses its ideal characteristics with the increase of the size of the array. Abstract : Highlights: Wave energy arrays of different sizes and device slenderness are analysed using realistic wave resources. The evolution of hydrodynamic interactions is studied as a function of inter-device distances between the devices. Three different regions with particular characteristics (short, intermediate and long region) have been identified.